Praktik Konstruksi Berkelanjutan di Indonesia: Kajian Literatur Komprehensif - Indah, Risma Nur; Widyaningsih, Yulia (Universitas Kristen Maranatha, 2025)
The construction industry in Indonesia is currently growing rapidly in line with economic expansion and infrastructure acceleration. Sustainable construction is a principle implemented to minimize the adverse effects of construction activities. In order to support sustainable construction in Indonesia, up-to-date knowledge regarding its comprehensive implementation is essential. This research is conducted to understand the current status, obstacles, opportunities, and strategies in sustainable construction practices in Indonesia based on the literatures available. The first stage of this research involves identifying publications related to sustainable construction in Indonesia. Subsequently, bibliographic analysis and content analysis are conducted to address the research questions The results of the discussion show that sustainable construction practices recorded by research are still limited.. The main obstacles to the adoption of sustainable construction are the lack of expertise in this field and significant costs. The main strategies that can be employed include government commitment, both through providing incentives to address high investment costs and through the creation of specific and targeted regulations. Another factor that can promote the implementation of sustainable construction in Indonesia is stakeholder management, training, and education for the construction practitioners.